First steps towards intercultural education in Vietnam: exploring primary education teachers' level of intercultural competence (Primeros pasos hacia una educacion intercultural en Vietnam: explorando la competencia intercultural de los maestros de primaria) - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Improving teachers' intercultural competence is one of the keys for successful implementation of intercultural education. This paper explores Vietnamese primary education teachers' level of intercultural competence as one of the first steps towards intercultural education in this country. The ISS-15 questionnaire was used to collect data from 70 teachers working in different schools and English centres in Hanoi City. Data were analysed through descriptive statistics: one-way ANOVA and Kruskal-Wallis test. Results show homogeneity although teachers' backgrounds and working contexts are varied. Teachers show high degrees of interaction engagement and enjoyment as well as respect for cultural differences. However, their levels of interaction confidence and attentiveness are moderate. Our conclusions suggest that teachers need to develop their intercultural competence (IC), especially in terms of practice skills. They demand to implement intercultural education (IE) in Vietnamese schools, as well as to help citizens realize its outstanding role for the necessary socioeconomic changes of the country nowadays.
Keywords: intercultural competence; intercultural education; primary teachers; Vietnam